The Degree of Smart Phones Use in Education among the Students of Educational Technology at the Middle East University - Alassaf, Hamzeh Abdelfattah; Odeh, Fadi Abdelraheem (Advances in Social Sciences Research Journal, 2017)
The study measures the degree of smart phone use in education among the students of educational technology at Middle East University. To achieve the objective of the study, a questionnaire, comprising (20) items, was developed concerning the use of smart phones in education. The descriptive method was employed in the study through the distribution of questionnaires to all members of the study society for the academic year 2017/2016. The total number of completed questionnaires was (58). The results of the study showed that the degree of smart phones use for education among educational technology students at the Middle East University was medium. They also showed no significant differences at the level of (α ≤ 0.05) in the degree of smart phone use in the educational process from the students’ viewpoint that can be attributed to the variables of the study: gender and academic level. The study recommended holding courses for students to employ and use all the tools available in smart phones during the educational process.